2022
DOI: 10.3390/ijms23084259
|View full text |Cite
|
Sign up to set email alerts
|

Neuroepigenetic Mechanisms of Action of Ultrashort Peptides in Alzheimer’s Disease

Abstract: Epigenetic regulation of gene expression is necessary for maintaining higher-order cognitive functions (learning and memory). The current understanding of the role of epigenetics in the mechanism of Alzheimer’s disease (AD) is focused on DNA methylation, chromatin remodeling, histone modifications, and regulation of non-coding RNAs. The pathogenetic links of this disease are the misfolding and aggregation of tau protein and amyloid peptides, mitochondrial dysfunction, oxidative stress, impaired energy metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 170 publications
0
6
0
Order By: Relevance
“…In vitro and in vivo studies revealed the efficacy of the EDR peptide in neurodegenerative diseases. In addition, the EDR peptide is administered orally in older age groups as a part of the complex therapy in cerebral pathology, and in athletes, to increase endurance [ 26 , 27 ]. The KE-17 peptoid ( Figure 1 B), a KE dipeptide with a modified peptide bond, possessing retinal protective properties, has the highest LAT2 affinity among the investigated USPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and in vivo studies revealed the efficacy of the EDR peptide in neurodegenerative diseases. In addition, the EDR peptide is administered orally in older age groups as a part of the complex therapy in cerebral pathology, and in athletes, to increase endurance [ 26 , 27 ]. The KE-17 peptoid ( Figure 1 B), a KE dipeptide with a modified peptide bond, possessing retinal protective properties, has the highest LAT2 affinity among the investigated USPs.…”
Section: Resultsmentioning
confidence: 99%
“…PEPT2 is predominantly localized in the kidneys. PEPT1 is a low-affinity transporter of di- and tri-peptides, while PEPT2 is a high-affinity transporter of USPs [ 26 ]. In this condition, it would be reasonable to expect that the results of docking of the 26 biologically active USPs into the active site of PEPT2 ( Table 7 ) would be similar to those obtained for PEPT1 ( Table 5 ), which turned out to be incorrect.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, there is a growing demand for peptide-based compounds to treat a wide variety of neuronal conditions (Table 1). 62 Gonadotropin releasing hormone, vasopressin, melanotropin release-inhibiting factor (MIF-1) and neurokinin 1 antagonists are a few peptide based endogenous ligands found in the CNS that have shown potential in neurodegenerative diseases. Synthetic peptides have been investigated as therapeutic agents and tools for drug delivery and imaging in various neurodegenerative disorders, such as AD, PD, Huntington's disease, ALS, and multiple sclerosis (MS), as well as in conditions such as stroke, traumatic brain injury (TBI), and spinal cord injury (SCI).…”
Section: Peptides In Neurodegenerative Diseasesmentioning
confidence: 99%
“…3]. 64 Studies have demonstrated that two short amylin receptor antagonist peptides, SQELHRLQTYPR (7) and LGRLSQELHRLQTY (8), possess neuroprotective effects against Aβ toxicity, reduce neuroinflammation, restore neuroplasticity, and improve spatial memory in 5xFAD mice (AD model). 65 Zhang et al have reported a copper binding peptide, which has been explored through phage display library screening.…”
Section: Admentioning
confidence: 99%
“…Recently, bioactive materials have garnered widespread attention as functional molecules and have gradually been adopted for biomedical use, including in the treatment of immunodeficiency-related illnesses, accelerated osteogenic differentiation of mesenchymal stem cells, improved tissue vascularization, and promotion of nerve regeneration [ [10] , a) , b) ]. In this study, we designed an ultrashort peptide (Ser-Glu-Ser-Ser-Glu, SESSE) with the ability to promote M2 type macrophage polarization and BMSC differentiation ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%